A Quantitative Analysis of Animation Deformity in Prosthetic Breast Reconstruction. Issue 2 (August 2019) - Kim, John Y. S.; Qiu, Cecil S.; Chiu, Wen-Kuan; Feld, Lauren N.; Mioton, Lauren M.; Kearney, Aaron; Fracol, Megan
Abstract : Background: Animation deformity is characterized by implant deformity with pectoralis contraction after subpectoral implant-based breast reconstruction. Extant methods to measure and analyze animation deformity are hampered by the paucity of objective, quantitative data. The authors endeavored to supplement subjective measures with an in-depth quantitative analysis. Methods: Patients undergoing subpectoral implant-based breast reconstruction were followed prospectively with video analysis of animation deformity. Nipple displacement and surface area of contour deformity in resting and contracted states were quantified using imaging software. Degree of animation was compared to breast size, body mass index, division of pectoralis muscle, complications, and radiation therapy. Results: One hundred forty-five reconstructed breasts (88 patients) were analyzed. Mean nipple displacement was 2.12 ± 1.04 cm, mean vector of nipple displacement was 62.5 ± 20.6 degrees, and mean area of skin contour irregularity was 16.4 ± 15.41 percent. Intraoperative pectoralis division, smooth/round implants, and bilateral reconstructions were associated with greater deformity. A three-tiered grading system based on thresholds of 2-cm net nipple displacement and 25 percent skin contour irregularity placed 41.4 percent of breasts in grade 1, 35.9 percent in grade 2, and 22.8 percent in grade 3. Interrater variability testing demonstrated 89.5 percent overall agreement (kappa = 0.84). Conclusions: This study presents the first quantitative analysis of animation deformity in prosthetic breast reconstruction. Geometric analysis of nipple displacement vector and increasing animation with pectoralis division both implicate the inferior pectoralis myotome as a primary driver of animation deformity. A concomitant grading schema was developed to provide a standardized framework for discussing animation from patient to patient and from study to study. Abstract : Supplemental Digital Content is available in the text.